Environmental Archaeology - Reitz, Elizabeth J.; Shackley, Myra (Springer, 2020)
One of the most significant developments in archaeology in recent years is the emergence of its environmental branch: the study of humans’ interactions with their natural surroundings over long periods and of organic remains instead of the artifacts and household items generally associated with sites. With the current attention paid to human responsibility for environmental change, this innovative field is recognized by scientists, conservation and heritage managers and policymakers worldwide. In this context comes Environmental Archaeology by Elizabeth Reitz and Myra Shackley, updating the seminal 1981 text Environmental Archaeology by Myra Shackley. Rigorously detailed yet concise and accessible, this volume surveys the complex and technical field of environmental archaeology for researchers interested in the causes, consequences and potential future impact of environmental change and archaeology. Its coverage acknowledges the multiple disciplines involved in the field, expanding the possibilities for using environmental data from archaeological sites in enriching related disciplines and improving communication among them. Introductory chapters explain the processes involved in the formation of sites, introduce research designs and field methods and walk the reader through biological classifications before focusing on the various levels of biotic and abiotic materials found at sites, including: Sediments and soils. Viruses, bacteria, archaea, protists and fungi. Bryophytes and vascular plants. Wood, charcoal, stems, leaves and roots. Spores, pollen and other microbotanical remains. Arthropods, molluscs, echinoderms and vertebrates. Stable isotopes, elements and biomolecules. The updated Environmental Archaeology is a major addition to the resource library of archaeologists, environmentalists, historians, researchers, policymakers—anyone involved in studying, managing or preserving historical sites. The updated Environmental Archaeology is a major addition to the resource library of archaeologists, environmentalists, historians, researchers, policymakers—anyone involved in studying, managing, or preserving historical sites